Multifunctional Digital Protection Relay for Voltage and Current Disturbances in Power Networks - Riza, Andrian; Suhariningsih; Okky Anggriawan, Dimas; Sunaryo, Epyk (Emitor: Jurnal Teknik Elektro, 2024)
The protection system is an essential part of the electrical power system, designed to minimize disturbances quickly, accurately, and precisely. Excessive electricity use can lead to frequent voltage and current fluctuations, resulting in short circuits, significant current spikes, and equipment damage. In addition to voltage and current variations, some electrical equipment is highly sensitive to frequency changes. Therefore, a device is needed to provide protection, prevent damage to electrical equipment, and ensure reliability. This research focuses on developing a protection relay using digital technology to continuously monitor and analyze voltage, current, and frequency parameters. When a fault or an out-of-range parameter is detected, the relay activates to protect the electrical system. For current protection, an experiment with a standard inverse setting at four different points was conducted, achieving an average reliability of 7.5%. For the very inverse setting with four different points, the average reliability was 5.79%. Voltage testing involved setting the overvoltage to the standard value of 231 volts and using various time delay types, resulting in an average reliability of 6%. This device is expected to protect electrical equipment that is highly sensitive to current, frequency, and voltage fluctuations.